Urban poverty: a case study of major cities in Malaysia - Pramanik, Ataul Huq; Abdullah, Moha Asri; Mat Derus, Alias; Barom, Mohd. Nizam (IIUM Press, 2009)
Urban poverty is inextricably linked to rural poverty. In fact, the former is caused by the latter. The ‘Pull’ and the ‘Push’ factors can significantly explain the prevailing dismal conditions associated with urban poverty. While the goal of faster development manifest through commercialization, modernization and urbanization contributed to urban-biased development strategy the lack of appropriate priorities for rural/agricultural development contributed to the ‘Push’ factors. Based on the detailed findings on multi-dimensional aspects of urban poverty this study strongly suggests that the development should be taken to the people and not the people to the development mostly confined to the urban areas. This will, on the one hand, reduce the justification for growing allocations for urban-biased industrialization strategy and weaken the ‘Push’ factors related to one way ‘rural to urban flow’ of the aspiring younger generation, on the other. The problems of over urbanization with the concomitant effects on poor living environments in ramshackle houses in squats, giving rise to growing social and moral degradations can be largely overcome by redirecting priorities for improving human capital as well as enhancing economic opportunities for the rural and urban poor, in general and those from less developed regions, in particular.